GAYA BAHASA PERBANDINGAN PADA NOVEL KISAH YANG PILU UNTUK KITA YANG RAGU KARYA BOY CANDRA - Salsabila, Elsya; Hidayatullah, Maikel; Riadi, Bambang; Prayogi, Rahmat (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to describe and analyze the forms and functions of comparative figurative language used in Boy Candra’s novel Kisah yang Pilu untuk Kita yang Ragu (A Sorrowful Story for Our Doubt). The focus of this research is to reveal how comparative figurative language strengthens emotional expression, enhances linguistic beauty, and builds aesthetic meaning in modern literary works. This study employs a qualitative approach using content analysis combined with a phenomenological perspective. Data were collected through intensive reading and note-taking of quotations containing comparative figurative language within the novel’s text. The results show that there are seven types of comparative figurative language found in the novel, namely simile, metaphor, personification, antithesis, tautology, and anticipation, with a total of 19 data instances. The most dominant types are simile, metaphor, and personification, which are used to depict the characters’ emotional states and to create poetic beauty in the narrative. Meanwhile, figures such as antithesis, tautology, and anticipation serve to reinforce meaning and provide stylistic variation in the author’s expression. The novelty of this research lies in combining stylistic analysis with a phenomenological approach to uncover the emotional and psychological meanings behind the use of comparative figurative language in contemporary Indonesian popular fiction.